Key Enablers of the European Security Industry Performance - Carlos Martí Sempere (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
One of the research areas of the New Agenda for European Security Economics (EUSECON) is society's response to insecurity. Solutions to enhance security often involve the development and supply of specific goods and services. This has led to an industry which has progressively evolved through the 20th century. Yet, after the 9/11 attacks, the security industry was subject to growing demand. Moreover, it raised the interest of academics and policy makers aimed at assessing its performance in terms of the efficient supply of sound security solutions. This briefing summarizes the main findings of the research already conducted, highlighting key issues for policies focused on enhancing this industry.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330